Pengaruh Risiko Environment Social and Governance Terhadap Kinerja Keuangan Perusahaan (Studi Pada Perusahaan Didalam Indeks IDXESGL) - Fahry Priandhana (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2022)
This study aims to analyze the effect of ESG risk on the financial performance of companies. The object of this research is companies listed on the Indonesian Stock Exchange and included in the IDXESGL index. The total sample in this study is 24 companies. The independent variable in this research is ESG risk where the data is available and generated from the Indonesian Stock Exchange cooperation with Sustainalytics. The independent variable in this study is the performance of the company represented by the ROA (Return on Asset) obtained by dividing profits by total assets. Data analysis was performed using simple linear regression and Microsoft Excel. The results of data analysis show that there is a negative effect of ESG risk on the company's financial performance. Thus, the higher the ESG risk of a company, the financial performance of the company will decrease. However, the effect of ESG risk on a company's financial performance is not significant.